Family Medicine Clerkship Preceptors’ Experiences Welcoming and Supporting Medical Students of Color - Toby Keys; Sarah Maeda; Meagan Johnson; Genya Shimkin; Jamella Gow; Joel Carey (Journal of Regional Medical Campuses, 2024)
Purpose: Medical students of color (MSoC) regularly experience discrimination and mistreatment during medical school. Preceptors have the potential to provide meaningful support for MSoC while on their family medicine clerkship rotation.  This mixed-method study explores family medicine clerkship preceptors’ challenges, current practices, and institutional needs related to welcoming and supporting MSoC.